Carcinosarcoma of the Uterus: An Elusive Diagnosis - Bhattarai, Anupama; Pariyar, Jitendra; Neupane, Sameer; Koirala, Srijana; Pokhrel, Pratit; Pandit, Subhas (Nepalese Journal of Cancer, 2020)
Introduction: Carcinosarcoma or Malignant Mixed Mullerian Tumor (MMMT) of the uterus is a rare malignant tumor comprising both carcinomatous and sarcomata’s components. Worldwide it accounts for two to five percentages of all uterine malignancies. However, there is a paucity of reports in Nepalese literature. Case report: A 62 year’s postmenopausal woman with diabetes and hypertension presented with urinary symptoms for two months and passage of fleshy mass per vagina for two days. Ultrasound was inconclusive, whereas, Magnetic Resonance Imaging (MRI) showed an endo-cervical mass. Pre-operative biopsy of the masssuggested leiomyosarcoma. Abdominal hysterectomy with bilateral salpingo-oophorectomy and pelvic andpara-aortic lymphadenectomy was performed. Per-operatively, an atrophic uterus, a dimple in the funds, andballooning of the lower uterine segment and vagina were noted. The cut section showed an exophytic polypoidalmass with base in the fundus. Histopathology revealed Stage IA carcinosarcoma with aggressive mitotic figures. Immunohistochemistry confirmed the diagnosis of carcinosarcoma with a heterogonous rhabdomyosarcomatouscomponent. Adjuvant chemotherapy and radiation therapy was advised. Conclusion: The preoperative diagnosis of carcinosarcoma or MMMT was difficult and might be missed on biopsy as well. Owing to its aggressive nature and higher rates of post-surgical recurrence, carcinosarcoma accounts for around one-fifth of deaths due to uterine malignancies. Surgery is the primary treatment modality, yet much study is needed before evidence-based adjuvant management for improving its outcome is established.